Socio-economic and Demographic status of Emigrants’ Households of Baghchaur Municipality - Raut, Rekha (Educational Journal, 2023)
This study deals with the “International Labour Migration (A Case Study of Baghchaur Municipality in Salyan District. The primary data was collected from the study area of Baghchaur Municipality. The general objective of the study is to examine the scenario of international labour migration pertaining to study area. Main objectives of the study are to examine the socio-economic and demographic status of emigrant's households, influencing factors, direction and magnitude, and the impact of emigration in the place of origin. The analysis and interpretation of data were carried out by using frequency tables, cross tabulation, with selected dependent and independent variables. International labour migration is seen in direction and destination with increasing volume in study side. Methods: Simple random sampling procedure was applied to collect the primary data and information about the emigrants by using questionnaire. Descriptive research design was used and the total number of international labor migrants were 118 from 100 households. There are 118 respondents were found whereas 111 were male and 7 were female. Results: India has the highest volume of emigrants and the flow is increasing now towards Malaysia from Nepal. Skilled migrant workers get high paid jobs. Reliability of human resource agencies have also played the crucial role in finding the work and wage. Amount, frequency and regularity of remittances depend upon the types of works, companies and the destination country. International money express, banks, and western union money transfer are mostly used channels for sending money. The rise in income is evident in the emigrant's household but the expenditure increasing. Unemployment, insufficient agricultural land and poverty are the key factors for emigration associated with origin. Due to the low level of education migrant workers get highly paid in destination countries compared to Nepal. Availability of unskilled works in the destination countries seems appealing to the low educated migrant workers.